Active-Site Inhibitors Modulate the Dynamic Properties of Human Monoacylglycerol Lipase: A Hydrogen Exchange Mass Spectrometry Study - Karageorgos, Ioannis (2013)
Human monoacylglycerol lipase (hMGL) regulates endocannabinoid signaling primarily by deactivating the lipid messenger 2-arachidonoylglycerol. Agents that carbamylate hMGLs catalytic Ser(122) constitute a leading class of therapeutically promising hMGL inhibitors. We have applied peptide-level hydrogen/deuterium exchange mass spectrometry to characterize hMGL’s conformational responses to two potent carbamylating inhibitors, AM6580 (irreversible) and AM6701 (slowly reversible). A dynamic, solvent-exposed lid domain is characteristic of hMGL’s solution conformation. Both hMGL inhibitors restricted backbone enzyme motility in the active-site region and increased substrate binding-pocket solvent exposure. Covalent reaction of AM6580 with hMGL generates a bulkier carbamylated Ser(122) residue as compared to the more discrete Ser(122) modification by AM6701, a difference reflected in AM6580’s more pronounced effect upon hMGL conformation. We demonstrate that structurally distinct carbamylating hMGL inhibitors generate particular conformational ensembles characterized by regionspecific hMGL dynamics. By demonstrating the distinctive influences of two hMGL inhibitors on enzyme conformation, this study furthers our understanding at the molecular level of the dynamic features of hMGL interaction with small-molecule ligands. [Image: see text]